Teaching EFL/ESL in the Digital Age: Education Post COVID-19 Pandemic - Nada Mohsen Sherif (Journal of English Language Teaching and Linguistics, 2023)
The education industry is one of the sectors heavily affected by the COVID-19 pandemic. Thanks to the advancement of educational technologies and global collaborations, teachers managed to shift to distance teaching to mitigate the effect of the worldwide school closures. This sudden shift revealed the glory of the Digital Age and the need to upskill teachers and learners to compete in the future job market. This paper discusses the emerging skills needed for the future and investigates the perceptions of EFL/ESL teachers about their current education environment status post-COVID-19 pandemic along with their student’s digital skills. This study adopts a descriptive quantitative approach. The research instrument used is a survey to collect the perspectives of non-native EFL/ESL teachers and instructors working in developing countries about their current education environment post-COVID-19 pandemic. The survey was in the form of a close-ended descriptive questionnaire including four sections. The findings reveal that future jobs are based on high cognitive skills that need to be implemented in today’s learners. High awareness of the importance of continuous professional development and the need for further digital up skilling of learners, practitioners, and workspaces were also reported. Further studies with broader samples of EFL/ESL teachers are recommended.